Vegetationskundliche und palynologische Befunde aus dem Muktinath-Tal (Tibetischer Himalaya, Nepal).: Ein Beitrag zur Landschaftsgeschichte altweltlicher Hochgebirgshalbwüsten - Miehe, Georg; Miehe, Sabine; Schlütz, Frank (ERDKUNDE, 2002)
Sub-desertic thorny dwarf-shrublands characterise the arid high mountains between the Atlas and southern Tibet. In the Muktinath valley and within the entire Mustang district of N Nepal, they are represented by Caragana gerardiana -Igelheiden ('porcupine heath'). The question to which extent these sub-desertic shrublands are natural, is discussed in 3 approaches: (1) by comparative records and observations of the present vegetation along altitudinal and humidity gradients, (2) by interpretation of a pollen diagram from Jharkot, (3) by consideration of archaeological findings. Probably the lower part of the pollen profile documents the development of the Holocene primary forests until the formation of Pinus wallichiana forests in the surroundings of Jharkot during the middle-holocene climatic optimum. With good reliability, the clearing of the pine forests and the onset of pastoral land use around 5400 BP is proven (some 1,900 years prior to the earliest archaeological datings). With a certain probability, barley cultivation started at latest around 4500 BP. Since this initial occupation, at least the slopes below Jharkot remained devoid of forests. Pollen of the Caragana type first appears around 3200 BP. It is well imaginable that the Caragana thorn shrubs were introduced by the livestock accompanying new settlers, whose presence is also archaeologically documented in this period. From relict trees and indicative herbaceous species in the present vegetation it can be concluded that not only the relatively humid Muktinath valley, but the entire southern Mustang area could still support trees, at least open Cupressaceae stands. Consequently, the Caragana thorn formations represent a secondary vegetation up to the drought limit of tree growth (250 mm annual precipitation at most). In N Mustang, however, Caragana gerardiana grows beyond the drought limit of Juniperus indica in the dry valley ground, proving its nature of a semi-desert species. Its spreading into the forest belt has been favoured by human activities (woodcutting and livestock grazing) for at least 3,200 years.